2014
DOI: 10.1155/2014/945829
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Two Different Transfusion Strategies on Patient Immune Response during Major Abdominal Surgery: A Preliminary Report

Abstract: Blood transfusion is associated with well-known risks. We investigated the difference between a restrictive versus a liberal transfusion strategy on the immune response, as expressed by the production of inflammatory mediators, in patients subjected to major abdominal surgery procedures. Fifty-eight patients undergoing major abdominal surgery were randomized preoperatively to either a restrictive transfusion protocol or a liberal transfusion protocol (with transfusion if hemoglobin dropped below 7.7 g dL−1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Transfusions can still cause alloimmunization, transmission of viral diseases, graft-versushost disease, and an increased post-operative infection rate. 4,6,7,55 It is important to make an individualized decision on the use of blood transfusion in every patient undergoing cancer surgery, in conjunction with other precautionary measures. 5 This retrospective study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfusions can still cause alloimmunization, transmission of viral diseases, graft-versushost disease, and an increased post-operative infection rate. 4,6,7,55 It is important to make an individualized decision on the use of blood transfusion in every patient undergoing cancer surgery, in conjunction with other precautionary measures. 5 This retrospective study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative blood transfusions with packed red blood cells (pRBC) are used to compensate for critical blood loss, but have been associated with increased risk of tumor recurrence and decreased long-term outcome in several tumor types, including colorectal, prostate, lung, and head and neck cancer. [4][5][6][7][8][9][10][11] The effect of blood transfusions on prognosis is attributed to a distinct pathology of immunosuppression, known as transfusion-related immune modulation (TRIM). Blood transfusion seems to provoke an immune deviation 12 and changes in the anti-inflammatory/proinflammatory environment.…”
Section: Introductionmentioning
confidence: 99%
“…We grouped the published studies into three groups (Table 1) [34567891011121314151617181920212223242526272829303132333435363738394041424344454647484950515253545556575859606263646566676869707172737475767778798081]. The first group included studies that identified the characteristics of hosts exhibiting inflammation, the second group included studies that measured the effect of treatment interventions, and the third group included studies that predicted the outcomes of interventions.…”
Section: Factors Associated With Inflammation In Patients With Cancermentioning
confidence: 99%
“…By contrast, the studies that found no effect, mixed effects, or immune‐suppressive effects associated with RBC transfusion largely employed leukoreduced RBC products . Immunosuppressive effects of transfusion have been studied most often in surgical patients . Whether these patients are more prone to immunosuppressive effects of RBC transfusion, or that other patient populations are understudied, is not clear.…”
Section: The Dynamic Immune Response To Critical Illnessmentioning
confidence: 99%
“…Whether these patients are more prone to immunosuppressive effects of RBC transfusion, or that other patient populations are understudied, is not clear. Different immunosuppressive effects of transfusion have been observed, including decreased ability of immune cells to produce proinflammatory cytokines, increased production of anti‐inflammatory cytokines, and decreased function of T lymphocytes and NK cells . ‐ Effects of storage duration in the context of RBC TRIM are unclear, with some studies indicating a storage effect, while others do not.…”
Section: The Dynamic Immune Response To Critical Illnessmentioning
confidence: 99%